2014
DOI: 10.1186/1756-3305-7-309
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic study of six species of Anopheles mosquitoes in Peninsular Malaysia based on inter-transcribed spacer region 2 (ITS2) of ribosomal DNA

Abstract: BackgroundMolecular techniques are invaluable for investigation on the biodiversity of Anopheles mosquitoes. This study aimed at investigating the spatial-genetic variations among Anopheles mosquitoes from different areas of Peninsular Malaysia, as well as deciphering evolutionary relationships of the local Anopheles mosquitoes with the mosquitoes from neighbouring countries using the anopheline ITS2 rDNA gene.MethodsMosquitoes were collected, identified, dissected to check infection status, and DNA extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…cracens, PCR was carried on targeted atITS2 gene. The ITS2 was amplified using primers ITS2A (5' TGTGAACTGCAGGACA 3') and ITS2B (5' TATGCTTAAATTCAGGGGGT 3') [11], [12]. Each reaction mixture of 50 µL contained 5 µL of mosquito DNA template, primers ITS2A and ITS2B, 0.2 µM respectively, and 25 µl 2× MyTaq Mix (Bioline, USA).…”
Section: Molecular Identification and Sequencing Targeting The Internmentioning
confidence: 99%
See 1 more Smart Citation
“…cracens, PCR was carried on targeted atITS2 gene. The ITS2 was amplified using primers ITS2A (5' TGTGAACTGCAGGACA 3') and ITS2B (5' TATGCTTAAATTCAGGGGGT 3') [11], [12]. Each reaction mixture of 50 µL contained 5 µL of mosquito DNA template, primers ITS2A and ITS2B, 0.2 µM respectively, and 25 µl 2× MyTaq Mix (Bioline, USA).…”
Section: Molecular Identification and Sequencing Targeting The Internmentioning
confidence: 99%
“…An. cracens from all localities was subjected for molecular analysis based on inter-transcribed spacer region 2 (ITS2) of ribosomal DNA [11]- [13] in order to confirm the species. Figure 3 showed that those mosquitoes were confirmed as An.…”
Section: Anopheles Nemophilousmentioning
confidence: 99%
“…The molecular marker rDNA-ITS2 is used in molecular taxonomy for separating sibling species (2), in phylogeny for establishing evolutionary relationships among mosquito species (3), and in phylogeography and population genetics for assessing the geographic distribution of mosquitoes (4).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mosquito barcoding studies have used both mitochondrial and nuclear markers to distinguish species (Foley et al 2007; Paredes-Esquivel et al 2009; Puslednik et al 2012; Bourke et al 2013). ITS2 is often used in mosquito studies as its high evolutionary rate makes it useful for investigating closely related species, such as those in the Anopheles genus (Wilkerson et al 2004; Marrelli et al 2006; Walton et al 2007; Sum et al 2014). …”
mentioning
confidence: 99%